Lamalle’s Historiographical Considerations in the Preface to Pio Paschini’s Vita e opere di Galileo Galilei Comparing Historiographical Approaches - MARCOLINI, LORENZO (Gjornâl Furlan des Siencis - Friulian Journal of Science, 2021)
The case of the work on Galilei delivered by Pio Paschini in 1944 for printing but then published twenty years later is little known outside the Catholic ecclesial world. But it is a story that stimulates, even seventy years later, questions about the limits of scientific knowledge and the influence of scientific discoveries on both society and the relationship between science and religion. The book was published by the Pontifical Academy of Sciences, the same one that had decided twenty years earlier to archive it. Fr. Edmond Lamalle, a Jesuit and historian of science, was commissioned to edit the publication, inserting appropriate updating notes required by the new historiographical lines. Lamalle not only introduced appropriate critical notes in his preface, he also inserted corrections and additions into the original text, highlighted by the attentive eye of Monsignor Pietro Bertolla and brought to the stage at the centenary congress of the Carnic prelate’s birth. Lamalle’s hand fits right in where the author recounts the development of the famous trial suffered by Galilei before the Tribunale del Sant’Ufizio, seen by the scientific world as proof of an irremediable conflict between science and religion. In this article, the author, fifty years after the publication of the Paschinian work, notes the need to reread the Jesuit scholar’s judgments from within a world profoundly changed, above all by the technological connotation of our society and by new contributions and studies on scientific epistemology and the Galilei case. The rereading of his preface, therefore, lent itself to personal reflection. .